1996
DOI: 10.1055/s-2007-973785
|View full text |Cite
|
Sign up to set email alerts
|

Leber Congenital Amaurosis - Differential Diagnosis, Ophthalmological and Neuroradiological Report of 18 Patients

Abstract: Between 1985 and 1995 eighteen babies, presenting to our department with absent visual contact and roving eye movements, showed a non-recordable flash electroretinogram (fERG). This was confirmed when repeated after a one-year interval. In four patients with developmental delay an underlying systemic disorder was diagnosed after a thorough pediatric neurological evaluation: Senior Loken syndrome, neuroaxonal dystrophy, ceroid lipofuscinosis and a yet unclear metabolic disorder were the revised diagnoses. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 3 publications
(4 reference statements)
0
8
0
1
Order By: Relevance
“…Later reappraisals of children originally diagnosed as LCA with neurodevelopmental delay can reveal the presence of a syndrome that was not initially apparent,3 13 24 25 particularly when there was no initial genetic diagnosis to confirm non-syndromic LCA. In this study, we document neurodevelopmental delay in a subset of children with genetically confirmed LCA due to recessive RPGRIP1 and GUCY2D mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Later reappraisals of children originally diagnosed as LCA with neurodevelopmental delay can reveal the presence of a syndrome that was not initially apparent,3 13 24 25 particularly when there was no initial genetic diagnosis to confirm non-syndromic LCA. In this study, we document neurodevelopmental delay in a subset of children with genetically confirmed LCA due to recessive RPGRIP1 and GUCY2D mutations.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, these diseases need to be discriminated from LCA as an isolated ocular disease. However, occasionally, this differentiation cannot be achieved by clinical and paraclinical investigations, especially in the early childhood [23,24] . Moreover, to date, 321 genes and loci on RetNet database have been linked to inherited retinal dystrophies, which some of them such as early onset Retinitis pigmentosa (RP) and CRD may have similar features with LCA.…”
Section: Lc3288mentioning
confidence: 99%
“…The frequency and severity of CVH are unknown, as we excluded any patients in whom the status of the vermis could not be determined [Casteels et al, 1996;Clarke et al, 1992;Delaney et al, 1978;Fernandez-Rodriguez et al, 1990;Proesmans et al, 1975;Waldherr et al, 1982;Warady et al, 1994]. However, we expect all patients to have CVH and the associated brainstem malformation.…”
Section: Cerebello-oculo-renal (Hepatic) Syndromesmentioning
confidence: 99%